2005
DOI: 10.1159/000085187
|View full text |Cite
|
Sign up to set email alerts
|

Stuttering Frequency on Meaningful and Nonmeaningful Words in Adults Who Stutter

Abstract: Previous research has suggested that word meaning can influence the loci and frequency of stuttering moments. Based on this proposition, it was hypothesized that people who stutter will exhibit a larger proportion of stuttering moments on meaningful words when compared to nonmeaningful or nonsense words. In order to test this hypothesis, stuttering frequency was examined among 9 English-speaking adults who stutter as they read a total of 126 words that were either meaningful or nonmeaningful in nature. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In this study, no significant difference was observed between people who stutter and those who do not in terms of reaction time. Probably, the difference between the two groups in repeating non-words versus the repetition of words was due to differences in the methods used to access, retrieve, and execute words compared with those in the non-words [24]. Moreover, phonological decoding and encoding in non-words were different than words which could affect the severity of speech disfluency in people who stutter, because in non-words, the retrieval of semantic content (word meaning) was deleted in comparison with words, and the output of non-words was focused on phonological encoding [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no significant difference was observed between people who stutter and those who do not in terms of reaction time. Probably, the difference between the two groups in repeating non-words versus the repetition of words was due to differences in the methods used to access, retrieve, and execute words compared with those in the non-words [24]. Moreover, phonological decoding and encoding in non-words were different than words which could affect the severity of speech disfluency in people who stutter, because in non-words, the retrieval of semantic content (word meaning) was deleted in comparison with words, and the output of non-words was focused on phonological encoding [25].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is of great interest to investigate linguistic factors that may affect stuttering including word types, meaning, syntactic structure, syntactic complexity, length, syllabic structure and word loading data which have been examined in various studies. [11][12][13][14] Dworzynski et al 15 Stated that the occurrence of stuttering in conversation does not happen accidentally. 15 This has called for research addressing stuttering based on linguistic features.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches have indicated the relationship among the linguistic factors such as syntactic construct, syntactic complication, the position and type of word, the length of word, syllable structure and the informative load of the word with the stuttering (5)(6)(7)(8). Syllable structure of the word has a specific importance among the other linguistic factors, regarding the presence or absence of consonant cluster, because syllable structure is one of the most effective factors in phonological encoding, which can have an influence on the frequency of dis-fluency occurrences among people with stuttering.…”
Section: Introductionmentioning
confidence: 99%